If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(x + -5)(x + -1(3 + 2i))(x + -1(3 + -2i)) = 0 Reorder the terms: (2 + x)(x + -5)(x + -1(3 + 2i))(x + -1(3 + -2i)) = 0 Reorder the terms: (2 + x)(-5 + x)(x + -1(3 + 2i))(x + -1(3 + -2i)) = 0 (2 + x)(-5 + x)(x + (3 * -1 + 2i * -1))(x + -1(3 + -2i)) = 0 (2 + x)(-5 + x)(x + (-3 + -2i))(x + -1(3 + -2i)) = 0 Reorder the terms: (2 + x)(-5 + x)(-3 + -2i + x)(x + -1(3 + -2i)) = 0 (2 + x)(-5 + x)(-3 + -2i + x)(x + (3 * -1 + -2i * -1)) = 0 (2 + x)(-5 + x)(-3 + -2i + x)(x + (-3 + 2i)) = 0 Reorder the terms: (2 + x)(-5 + x)(-3 + -2i + x)(-3 + 2i + x) = 0 Multiply (2 + x) * (-5 + x) (2(-5 + x) + x(-5 + x))(-3 + -2i + x)(-3 + 2i + x) = 0 ((-5 * 2 + x * 2) + x(-5 + x))(-3 + -2i + x)(-3 + 2i + x) = 0 ((-10 + 2x) + x(-5 + x))(-3 + -2i + x)(-3 + 2i + x) = 0 (-10 + 2x + (-5 * x + x * x))(-3 + -2i + x)(-3 + 2i + x) = 0 (-10 + 2x + (-5x + x2))(-3 + -2i + x)(-3 + 2i + x) = 0 Combine like terms: 2x + -5x = -3x (-10 + -3x + x2)(-3 + -2i + x)(-3 + 2i + x) = 0 Multiply (-10 + -3x + x2) * (-3 + -2i + x) (-10(-3 + -2i + x) + -3x * (-3 + -2i + x) + x2(-3 + -2i + x))(-3 + 2i + x) = 0 ((-3 * -10 + -2i * -10 + x * -10) + -3x * (-3 + -2i + x) + x2(-3 + -2i + x))(-3 + 2i + x) = 0 ((30 + 20i + -10x) + -3x * (-3 + -2i + x) + x2(-3 + -2i + x))(-3 + 2i + x) = 0 (30 + 20i + -10x + (-3 * -3x + -2i * -3x + x * -3x) + x2(-3 + -2i + x))(-3 + 2i + x) = 0 Reorder the terms: (30 + 20i + -10x + (6ix + 9x + -3x2) + x2(-3 + -2i + x))(-3 + 2i + x) = 0 (30 + 20i + -10x + (6ix + 9x + -3x2) + x2(-3 + -2i + x))(-3 + 2i + x) = 0 (30 + 20i + -10x + 6ix + 9x + -3x2 + (-3 * x2 + -2i * x2 + x * x2))(-3 + 2i + x) = 0 Reorder the terms: (30 + 20i + -10x + 6ix + 9x + -3x2 + (-2ix2 + -3x2 + x3))(-3 + 2i + x) = 0 (30 + 20i + -10x + 6ix + 9x + -3x2 + (-2ix2 + -3x2 + x3))(-3 + 2i + x) = 0 Reorder the terms: (30 + 20i + 6ix + -2ix2 + -10x + 9x + -3x2 + -3x2 + x3)(-3 + 2i + x) = 0 Combine like terms: -10x + 9x = -1x (30 + 20i + 6ix + -2ix2 + -1x + -3x2 + -3x2 + x3)(-3 + 2i + x) = 0 Combine like terms: -3x2 + -3x2 = -6x2 (30 + 20i + 6ix + -2ix2 + -1x + -6x2 + x3)(-3 + 2i + x) = 0 Multiply (30 + 20i + 6ix + -2ix2 + -1x + -6x2 + x3) * (-3 + 2i + x) (30(-3 + 2i + x) + 20i * (-3 + 2i + x) + 6ix * (-3 + 2i + x) + -2ix2 * (-3 + 2i + x) + -1x * (-3 + 2i + x) + -6x2 * (-3 + 2i + x) + x3(-3 + 2i + x)) = 0 ((-3 * 30 + 2i * 30 + x * 30) + 20i * (-3 + 2i + x) + 6ix * (-3 + 2i + x) + -2ix2 * (-3 + 2i + x) + -1x * (-3 + 2i + x) + -6x2 * (-3 + 2i + x) + x3(-3 + 2i + x)) = 0 ((-90 + 60i + 30x) + 20i * (-3 + 2i + x) + 6ix * (-3 + 2i + x) + -2ix2 * (-3 + 2i + x) + -1x * (-3 + 2i + x) + -6x2 * (-3 + 2i + x) + x3(-3 + 2i + x)) = 0 (-90 + 60i + 30x + (-3 * 20i + 2i * 20i + x * 20i) + 6ix * (-3 + 2i + x) + -2ix2 * (-3 + 2i + x) + -1x * (-3 + 2i + x) + -6x2 * (-3 + 2i + x) + x3(-3 + 2i + x)) = 0 Reorder the terms: (-90 + 60i + 30x + (-60i + 20ix + 40i2) + 6ix * (-3 + 2i + x) + -2ix2 * (-3 + 2i + x) + -1x * (-3 + 2i + x) + -6x2 * (-3 + 2i + x) + x3(-3 + 2i + x)) = 0 (-90 + 60i + 30x + (-60i + 20ix + 40i2) + 6ix * (-3 + 2i + x) + -2ix2 * (-3 + 2i + x) + -1x * (-3 + 2i + x) + -6x2 * (-3 + 2i + x) + x3(-3 + 2i + x)) = 0 (-90 + 60i + 30x + -60i + 20ix + 40i2 + (-3 * 6ix + 2i * 6ix + x * 6ix) + -2ix2 * (-3 + 2i + x) + -1x * (-3 + 2i + x) + -6x2 * (-3 + 2i + x) + x3(-3 + 2i + x)) = 0 Reorder the terms: (-90 + 60i + 30x + -60i + 20ix + 40i2 + (-18ix + 6ix2 + 12i2x) + -2ix2 * (-3 + 2i + x) + -1x * (-3 + 2i + x) + -6x2 * (-3 + 2i + x) + x3(-3 + 2i + x)) = 0 (-90 + 60i + 30x + -60i + 20ix + 40i2 + (-18ix + 6ix2 + 12i2x) + -2ix2 * (-3 + 2i + x) + -1x * (-3 + 2i + x) + -6x2 * (-3 + 2i + x) + x3(-3 + 2i + x)) = 0 (-90 + 60i + 30x + -60i + 20ix + 40i2 + -18ix + 6ix2 + 12i2x + (-3 * -2ix2 + 2i * -2ix2 + x * -2ix2) + -1x * (-3 + 2i + x) + -6x2 * (-3 + 2i + x) + x3(-3 + 2i + x)) = 0 Reorder the terms: (-90 + 60i + 30x + -60i + 20ix + 40i2 + -18ix + 6ix2 + 12i2x + (6ix2 + -2ix3 + -4i2x2) + -1x * (-3 + 2i + x) + -6x2 * (-3 + 2i + x) + x3(-3 + 2i + x)) = 0 (-90 + 60i + 30x + -60i + 20ix + 40i2 + -18ix + 6ix2 + 12i2x + (6ix2 + -2ix3 + -4i2x2) + -1x * (-3 + 2i + x) + -6x2 * (-3 + 2i + x) + x3(-3 + 2i + x)) = 0 (-90 + 60i + 30x + -60i + 20ix + 40i2 + -18ix + 6ix2 + 12i2x + 6ix2 + -2ix3 + -4i2x2 + (-3 * -1x + 2i * -1x + x * -1x) + -6x2 * (-3 + 2i + x) + x3(-3 + 2i + x)) = 0 Reorder the terms: (-90 + 60i + 30x + -60i + 20ix + 40i2 + -18ix + 6ix2 + 12i2x + 6ix2 + -2ix3 + -4i2x2 + (-2ix + 3x + -1x2) + -6x2 * (-3 + 2i + x) + x3(-3 + 2i + x)) = 0 (-90 + 60i + 30x + -60i + 20ix + 40i2 + -18ix + 6ix2 + 12i2x + 6ix2 + -2ix3 + -4i2x2 + (-2ix + 3x + -1x2) + -6x2 * (-3 + 2i + x) + x3(-3 + 2i + x)) = 0 (-90 + 60i + 30x + -60i + 20ix + 40i2 + -18ix + 6ix2 + 12i2x + 6ix2 + -2ix3 + -4i2x2 + -2ix + 3x + -1x2 + (-3 * -6x2 + 2i * -6x2 + x * -6x2) + x3(-3 + 2i + x)) = 0 Reorder the terms: (-90 + 60i + 30x + -60i + 20ix + 40i2 + -18ix + 6ix2 + 12i2x + 6ix2 + -2ix3 + -4i2x2 + -2ix + 3x + -1x2 + (-12ix2 + 18x2 + -6x3) + x3(-3 + 2i + x)) = 0 (-90 + 60i + 30x + -60i + 20ix + 40i2 + -18ix + 6ix2 + 12i2x + 6ix2 + -2ix3 + -4i2x2 + -2ix + 3x + -1x2 + (-12ix2 + 18x2 + -6x3) + x3(-3 + 2i + x)) = 0 (-90 + 60i + 30x + -60i + 20ix + 40i2 + -18ix + 6ix2 + 12i2x + 6ix2 + -2ix3 + -4i2x2 + -2ix + 3x + -1x2 + -12ix2 + 18x2 + -6x3 + (-3 * x3 + 2i * x3 + x * x3)) = 0 Reorder the terms: (-90 + 60i + 30x + -60i + 20ix + 40i2 + -18ix + 6ix2 + 12i2x + 6ix2 + -2ix3 + -4i2x2 + -2ix + 3x + -1x2 + -12ix2 + 18x2 + -6x3 + (2ix3 + -3x3 + x4)) = 0 (-90 + 60i + 30x + -60i + 20ix + 40i2 + -18ix + 6ix2 + 12i2x + 6ix2 + -2ix3 + -4i2x2 + -2ix + 3x + -1x2 + -12ix2 + 18x2 + -6x3 + (2ix3 + -3x3 + x4)) = 0 Reorder the terms: (-90 + 60i + -60i + 20ix + -18ix + -2ix + 6ix2 + 6ix2 + -12ix2 + -2ix3 + 2ix3 + 40i2 + 12i2x + -4i2x2 + 30x + 3x + -1x2 + 18x2 + -6x3 + -3x3 + x4) = 0 Combine like terms: 60i + -60i = 0 (-90 + 0 + 20ix + -18ix + -2ix + 6ix2 + 6ix2 + -12ix2 + -2ix3 + 2ix3 + 40i2 + 12i2x + -4i2x2 + 30x + 3x + -1x2 + 18x2 + -6x3 + -3x3 + x4) = 0 (-90 + 20ix + -18ix + -2ix + 6ix2 + 6ix2 + -12ix2 + -2ix3 + 2ix3 + 40i2 + 12i2x + -4i2x2 + 30x + 3x + -1x2 + 18x2 + -6x3 + -3x3 + x4) = 0 Combine like terms: 20ix + -18ix = 2ix (-90 + 2ix + -2ix + 6ix2 + 6ix2 + -12ix2 + -2ix3 + 2ix3 + 40i2 + 12i2x + -4i2x2 + 30x + 3x + -1x2 + 18x2 + -6x3 + -3x3 + x4) = 0 Combine like terms: 2ix + -2ix = 0 (-90 + 0 + 6ix2 + 6ix2 + -12ix2 + -2ix3 + 2ix3 + 40i2 + 12i2x + -4i2x2 + 30x + 3x + -1x2 + 18x2 + -6x3 + -3x3 + x4) = 0 (-90 + 6ix2 + 6ix2 + -12ix2 + -2ix3 + 2ix3 + 40i2 + 12i2x + -4i2x2 + 30x + 3x + -1x2 + 18x2 + -6x3 + -3x3 + x4) = 0 Combine like terms: 6ix2 + 6ix2 = 12ix2 (-90 + 12ix2 + -12ix2 + -2ix3 + 2ix3 + 40i2 + 12i2x + -4i2x2 + 30x + 3x + -1x2 + 18x2 + -6x3 + -3x3 + x4) = 0 Combine like terms: 12ix2 + -12ix2 = 0 (-90 + 0 + -2ix3 + 2ix3 + 40i2 + 12i2x + -4i2x2 + 30x + 3x + -1x2 + 18x2 + -6x3 + -3x3 + x4) = 0 (-90 + -2ix3 + 2ix3 + 40i2 + 12i2x + -4i2x2 + 30x + 3x + -1x2 + 18x2 + -6x3 + -3x3 + x4) = 0 Combine like terms: -2ix3 + 2ix3 = 0 (-90 + 0 + 40i2 + 12i2x + -4i2x2 + 30x + 3x + -1x2 + 18x2 + -6x3 + -3x3 + x4) = 0 (-90 + 40i2 + 12i2x + -4i2x2 + 30x + 3x + -1x2 + 18x2 + -6x3 + -3x3 + x4) = 0 Combine like terms: 30x + 3x = 33x (-90 + 40i2 + 12i2x + -4i2x2 + 33x + -1x2 + 18x2 + -6x3 + -3x3 + x4) = 0 Combine like terms: -1x2 + 18x2 = 17x2 (-90 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -6x3 + -3x3 + x4) = 0 Combine like terms: -6x3 + -3x3 = -9x3 (-90 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4) = 0 Solving -90 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4 = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '90' to each side of the equation. -90 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + 90 + x4 = 0 + 90 Reorder the terms: -90 + 90 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4 = 0 + 90 Combine like terms: -90 + 90 = 0 0 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4 = 0 + 90 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4 = 0 + 90 Combine like terms: 0 + 90 = 90 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4 = 90 Add '-33x' to each side of the equation. 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + -33x + x4 = 90 + -33x Reorder the terms: 40i2 + 12i2x + -4i2x2 + 33x + -33x + 17x2 + -9x3 + x4 = 90 + -33x Combine like terms: 33x + -33x = 0 40i2 + 12i2x + -4i2x2 + 0 + 17x2 + -9x3 + x4 = 90 + -33x 40i2 + 12i2x + -4i2x2 + 17x2 + -9x3 + x4 = 90 + -33x Add '-17x2' to each side of the equation. 40i2 + 12i2x + -4i2x2 + 17x2 + -9x3 + -17x2 + x4 = 90 + -33x + -17x2 Reorder the terms: 40i2 + 12i2x + -4i2x2 + 17x2 + -17x2 + -9x3 + x4 = 90 + -33x + -17x2 Combine like terms: 17x2 + -17x2 = 0 40i2 + 12i2x + -4i2x2 + 0 + -9x3 + x4 = 90 + -33x + -17x2 40i2 + 12i2x + -4i2x2 + -9x3 + x4 = 90 + -33x + -17x2 Add '9x3' to each side of the equation. 40i2 + 12i2x + -4i2x2 + -9x3 + 9x3 + x4 = 90 + -33x + -17x2 + 9x3 Combine like terms: -9x3 + 9x3 = 0 40i2 + 12i2x + -4i2x2 + 0 + x4 = 90 + -33x + -17x2 + 9x3 40i2 + 12i2x + -4i2x2 + x4 = 90 + -33x + -17x2 + 9x3 Add '-1x4' to each side of the equation. 40i2 + 12i2x + -4i2x2 + x4 + -1x4 = 90 + -33x + -17x2 + 9x3 + -1x4 Combine like terms: x4 + -1x4 = 0 40i2 + 12i2x + -4i2x2 + 0 = 90 + -33x + -17x2 + 9x3 + -1x4 40i2 + 12i2x + -4i2x2 = 90 + -33x + -17x2 + 9x3 + -1x4 Reorder the terms: -90 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4 = 90 + -33x + -17x2 + 9x3 + -1x4 + -90 + 33x + 17x2 + -9x3 + x4 Reorder the terms: -90 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4 = 90 + -90 + -33x + 33x + -17x2 + 17x2 + 9x3 + -9x3 + -1x4 + x4 Combine like terms: 90 + -90 = 0 -90 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4 = 0 + -33x + 33x + -17x2 + 17x2 + 9x3 + -9x3 + -1x4 + x4 -90 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4 = -33x + 33x + -17x2 + 17x2 + 9x3 + -9x3 + -1x4 + x4 Combine like terms: -33x + 33x = 0 -90 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4 = 0 + -17x2 + 17x2 + 9x3 + -9x3 + -1x4 + x4 -90 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4 = -17x2 + 17x2 + 9x3 + -9x3 + -1x4 + x4 Combine like terms: -17x2 + 17x2 = 0 -90 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4 = 0 + 9x3 + -9x3 + -1x4 + x4 -90 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4 = 9x3 + -9x3 + -1x4 + x4 Combine like terms: 9x3 + -9x3 = 0 -90 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4 = 0 + -1x4 + x4 -90 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4 = -1x4 + x4 Combine like terms: -1x4 + x4 = 0 -90 + 40i2 + 12i2x + -4i2x2 + 33x + 17x2 + -9x3 + x4 = 0 The solution to this equation could not be determined.
| 23x-24x+2x=8x-7+2 | | X*25+.45=X*40+.25 | | -3x-5=6x+22 | | -2n+4(3-n)=2(4n+34) | | (x+30)/20=(2/4)x | | r+14=26 | | (x+30)/20=2/4x | | 9y+(-4x)-8x+1-5y+5= | | 5X+2Y=4Y | | Xlogy= | | 3x-10-x=8+4x-6 | | 26=r+14 | | 9x^2-0.64y^2=0 | | X+14=12-((9+(2-x))) | | 7-6n+3n=35-82 | | 5x+3x+20=90 | | 8+3x-2x+3=2x+2+18 | | x=7.65+-2y | | y(y-7)=-12 | | 94-74=28y-32y | | -5-5x=15x-6 | | V=93.5h | | 30.60=4x+8y | | .4x-7.5(x-1)=43 | | -20=45 | | 25/10=-1/2x | | 5(4.5+.9y)-1.9y=-29 | | 0.4x-7.5(x-1)=43 | | X(3x^3-6x)=0 | | p-59=34 | | (t+3)5/9=40 | | x+10y=30 |